2019
DOI: 10.1111/bjd.18476
|View full text |Cite
|
Sign up to set email alerts
|

Dupilumab in adolescents with uncontrolled moderate‐to‐severe atopic dermatitis: results from a phase II a open‐label trial and subsequent phase III open‐label extension

Abstract: Summary Background Dupilumab (monoclonal antibody inhibiting IL‐4/IL‐13 signalling) is approved for use in adolescents aged ≥ 12 years with inadequately controlled moderate‐to‐severe atopic dermatitis (AD). Dupilumab significantly improved AD signs/symptoms in a 16‐week, randomised, placebo‐controlled phase III trial in adolescents (NCT03054428). Objectives To characterize the pharmacokinetics of dupilumab, and long‐term safety and efficacy in adolescents. Methods This was a global, multicentre, phase IIa, ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
165
1
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(203 citation statements)
references
References 31 publications
24
165
1
13
Order By: Relevance
“…Dupilumab, a monoclonal antibody against interleukin-4 receptor alpha, has been used in numerous allergic diseases and works by blocking signaling of interleukin-4 and interleukin-13, type 2/Th2 cytokines. It has been confirmed to be effective in patients with moderate to severe AD in several double-blind, placebocontrolled studies and in clinical practice [43][44][45]. The result showed that clinical improvement is positively correlated with increased favorable microbial community and reduced abundance of S. aureus [46].…”
Section: Biological Therapy In Patients With Admentioning
confidence: 89%
“…Dupilumab, a monoclonal antibody against interleukin-4 receptor alpha, has been used in numerous allergic diseases and works by blocking signaling of interleukin-4 and interleukin-13, type 2/Th2 cytokines. It has been confirmed to be effective in patients with moderate to severe AD in several double-blind, placebocontrolled studies and in clinical practice [43][44][45]. The result showed that clinical improvement is positively correlated with increased favorable microbial community and reduced abundance of S. aureus [46].…”
Section: Biological Therapy In Patients With Admentioning
confidence: 89%
“…Dupilumab is also approved in the United States as an add-on treatment in patients aged ࣙ18 years with inadequately controlled chronic rhinosinusitis with nasal polyps. Clinical trials in adults [14][15][16][17][18] and adolescent populations 19,20 with moderate to severe AD, as well as in adult patients with asthma [21][22][23][24] and chronic rhinosinusitis with nasal polyps, 25,26 or eosinophilic esophagitis, 27 have demonstrated improvements in disease outcomes during dupilumab treatment, with an acceptable safety profile.…”
mentioning
confidence: 99%
“…In trials of dupilumab in moderate-to-severe AD, 60% of adults and 75% to 92% of adolescents had at least 1 comorbid allergic condition. 4 , 5 , 6 Of adolescents, 45% to 66% had comorbid AR, 35% to 61% had food allergy, 30% to 54% had asthma, and 0.4% had EoE. 4 , 5 However, nearly all trials have only evaluated the effects of dupilumab on a single disease entity per trial.…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 5 , 6 Of adolescents, 45% to 66% had comorbid AR, 35% to 61% had food allergy, 30% to 54% had asthma, and 0.4% had EoE. 4 , 5 However, nearly all trials have only evaluated the effects of dupilumab on a single disease entity per trial. In these studies, dupilumab dramatically improved disease severity and quality of life in AD, 4 , 5 , 6 asthma, 1 and CRwNP 3 with minimal side effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation